Sucrose/H+ and glucose/H+ symports at the plasma membrane of laticiferous cells and protoplasts of Hevea brasiliensis - Bouteau F; Bousquet U; Cornel D; Lacrotte R; Monestiez M; Rona J P (Indian Journal of Natural Rubber Research, 1992)
Polyisoprene synthesis in ethylene stimulated laticiferous cells of Hevea brasiliensis requires an exogenous supply of sugar. Plasmodesmata are absent from these non-chlorophyllian cells. The transplasmalemmal electrical gradient recorded at steady state was about-115 mV for laticiferous cells and -36mV for laticiferous protoplasts. Sucrose and glucose depolarize the plasmalemma of laticiferous cells by about 15 to 25 mV and by about 1 to 7 mV laticiferous protoplasts. Results show that with depolarization due to sucrose (1 mM) or glucose (1 mM), a slight alkalinization (0.1 to 0.2 pH units) can be detected on the outer surface of the cell. Fructose and 3-0-methyl-glucose have no such effect. The extent of depolarization due to the addition of sugars is lower than the electrogenic component of the membrane potential produced by the functioning of the H+-excretion pump (vandate sensitive-ATPase). Furthermore, in presence of vanadate or DNP, no shift in pH value was observed with glucose or sucrose. The effect of phlorizin on the shift of the membrane potential due to sugar uptake across the plasmalemma has been tested. Neither sucrose nor glucose demonstrate any depolarization and alkalinization in the presence of phlorizin. Stimulation of the H+-pump by ethylene hyperpolarizes cells by approximately -40mV and increases the extent of the depolarization induced by sugar transport. Even without the cellwall, with laticiferous protoplast, glucose and sucrose induce depolarization of plasmalemma. On these protoplasts, sugars do not induce any depolarization in the presence of DNP. These results suggest an active transport of the sugars from the apoplasm towards the cytosol. Evidence for the existence of H+ cotransport with sucrose and/or glucose at the plasmalemma is discussed.
Keywords: Ethylene; Ethylene; Hevea brasiliensis; Hevea brasiliensis; Laticiferous cells; Laticiferous cells; Laticiferous protoplasts; Laticiferous protoplasts; Membrane potential; Membrane potential; Phlorizin; Phlorizin